Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper, 2010)
Since its last report, the Independent Evaluation Office (IEO) has advanced work on the two current evaluations and selected topics for three new evaluations. The evaluations of Research at the IMF: Relevance and Utilization and IMF Performance in the Run-up to the Current Financial and Economic Crisis are in the concluding stages. IEO expects to send these evaluations to the Executive Board before year-end.